The Diversity and Abundance of Springtail (Collembola) on Forests and Smallholder in Jambi - Widrializa, .; Widyastuti, Rahayu; Santosa, Dwi Andreas; Djajakirana, Gunawan (JOURNAL OF TROPICAL SOILS, 2015)
Harapan forests is the first restoration forest in Indonesia, includes several different ecosystems. Different ecosystems have different characteristic to affect the diversity and abundance of Collembola. In the ecosystem, Collembola have an important role in biocontrol, decomposition, soil nutrient distribution, stimulation of soil microbial activity and as an alternative feed for predators. This study was aimed to investigate the diversity and abundance of Collembola in four ecosystems at Harapan forest, i.e. secondary forest, rubber forest, rubber smallholder and oil palm smallholder. To achieve the objective, soil samples were taken at 48 observation points in the four ecosystem. The soil samples were then extracted by Kempson Extractor. The diversity and abundance of Collembola in four ecosystems were categorized as medium to high. The total of individual and population of Collembola in the secondary and rubber forest ecosystems were likely to be higher than in the rubber and oil palm smallholders. This study had also identified four orders, 14 families and 31 genera of Collembola, where Isotomiella and Proisotoma dominated the genus of Collembola in the four ecosystems. [How to Cite: Widrializa, R Widyastuti, DA Santosa and G Djajakirana. 2015. The Diversity and Abundance of Springtail (Collembola) on Forests and Smallholder in Jambi. J Trop Soils 20: 173-180. Doi: 10.5400/jts.2015.20.3.173]Â